Implementation of E-Module with Flipped Classroom Model on Reproductive System Material to Improve Creative Thinking Skills and Learning Outcomes of Students - Wirda Hari Yani; Safrida; Muhubbudin M; M. Ali; Cut N (Postgraduate, University of Mataram, 2026)
This research aims to determine the differences in creative thinking abilities and learning outcomes improvement of students using an e-module with the flipped classroom model. The method employed in this research is experimental research. The research design is pretest-posttest group control design. The population of this study consists of eleventh-grade science students at MAN 2 Banda Aceh. Data collection on creative thinking abilities and learning outcomes is conducted using test instruments. Data analysis employs N-gain test and Mann Whitney test with a significance level of 0.05. The results of the data analysis indicate a significant difference between the experimental and control groups. The conclusion of this study is that there is a difference in creative thinking abilities and improvement in learning outcomes of students using an e-module with the flipped classroom model.